Patient-reported health problems and healthcare use after treatment for early-stage breast cancer. (August 2019) - de Ligt, K.M.; Heins, M.; Verloop, J.; Smorenburg, C.H.; Korevaar, J.C.; Siesling, S.
Abstract: Background: A clear picture of treatment-related health problems following breast cancer treatment is useful in anticipating the informational and other needs of patients during follow-up. This study aimed to identify treatment-related health problems in breast cancer patients up to five years after diagnosis. Secondly, the use of care associated with these health problems was identified. Methods: 876 surgically-treated female patients diagnosed between 2012 and 2016 with early-stage breast cancer were asked to complete an online survey about their current health problems and use of care. Multivariate logistic regression analyses were applied to determine the effect of patient and treatment characteristics on health problems. Results: 404 patients responded (46%). The median age was 62.0 years (SD:10.9). Apart from breast surgery, patients had been treated with radiotherapy (72%), chemotherapy (49%), anti-hormonal therapy (57%), and axillary dissection (21%). Ninety-three percent experienced one or more health problems. Over 50% of respondents experienced fatigue, psychological problems, and health problems regarding the breast, and/or musculoskeletal, central nervous, and reproductive system. Treatment with chemotherapy was significantly associated (p < 0.05) with an increased risk of health problems, respectively fatigue (OR:2.00), respiratory (OR:1.81), gastrointestinal (OR:1.87), central nervous (OR:3.40), and skin problems (OR:2.62). Use of healthcare for one or more health problems was reported by 64% of respondents. Discussion: Almost all patients experienced health problems up to five years after breast cancer diagnosis, with a range of complaints that were consistently present over time. Factors associated with the development of health problems are useful for better informing patients beforehand and targeting follow-up care. Highlights: Almost all breast cancer patients (93%) reported health problems during follow-up. Fatigue was the most reported health problem, reported by 63% of respondents. Health problems were presented consistently over time after diagnosis (<5 years). Especially chemotherapy was associated with an increased risk of health problems. Health care use was reported for half of the reported health problems.